2021
DOI: 10.1016/j.orgel.2020.106024
|View full text |Cite
|
Sign up to set email alerts
|

Low voltage operating organic light emitting transistors with efficient charge blocking layer

Abstract: Charge injection/blocking layers play important roles in the performances of organic electronic devices.Their incorporation into organic light emitting transistors has been limitted, due to generally high operating voltages (above 60 V) of these devices. In this work, two hole blocking molecules are integrated into tris-(8hydroxyquinoline) aluminum (Alq3) based light emitting transistors under operating voltage as low as 5 V. The effects of hole blocking and electron injection are decoupled through the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Non-planar asymmetric contacts were applied, with molybdenum oxide (MoO 3 )/Ag as the source electrode and lithium fluoride (LiF)/Al as the drain electrode. A hole blocking layer of Bathocuproine (BCP) was added following our previous study, which showed that blocking holes and efficiently injecting electrons can significantly enhance the optical performance of OLETs operating at low voltage . A 35 nm of anodized Al 2 O 3 passivated by polystyrene is proven to be an excellent dielectric bilayer with high capacitance (95 nF cm –2 ), low interface traps, and low leakage current, enabling the devices to operate at as low as 5 V.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-planar asymmetric contacts were applied, with molybdenum oxide (MoO 3 )/Ag as the source electrode and lithium fluoride (LiF)/Al as the drain electrode. A hole blocking layer of Bathocuproine (BCP) was added following our previous study, which showed that blocking holes and efficiently injecting electrons can significantly enhance the optical performance of OLETs operating at low voltage . A 35 nm of anodized Al 2 O 3 passivated by polystyrene is proven to be an excellent dielectric bilayer with high capacitance (95 nF cm –2 ), low interface traps, and low leakage current, enabling the devices to operate at as low as 5 V.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of high mobility charge transport layers have been applied, including small molecules, polymers, and metal oxides. Many OLETs reported so far work at relatively high operating voltages (≥60 V), which limits their practical use. To reduce the operating voltage, high-k dielectrics with polymer insulators or metal oxides have been explored. , Charge blocking/injection layers which are essential components in OLEDs can manifest their role in low-operating voltage OLETs . Contrary to OLETs, efficiency enhancement and color tuning in microcavity OLEDs are well-established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-bias (<10 V) OLET can be obtained using HfO x (k~12-23 depending on processing parameters) spin-coated from solution and passivated with a n-dodecylphosphonic acid (PA-C12)-SAM, which renders the topmost dielectric surface highly hydrophobic and facilitates the formation of the organic film [97]. Passivating the surface reduces the capacitance per unit area (from~200 nF/cm 2 to 160-170 nF/cm 2 ), on the other hand ensure lower leakage current in the dielectric layer (~10 −6 A/cm 2 ) [98].…”
Section: High-k Inorganic Dielectric Materials (Oxides Nitrides Etc)mentioning
confidence: 99%
“…Multilayer OLET structures, where charge transport and light generation can be decoupled and each allocated to different layers to promote exciton confinement in the emissive layer, show higher current densities and external quantum efficiency (EQE). It has been shown that these devices can outperform equivalent organic light-emitting diodes, with demonstrated potentials to achieve high luminance (>500 cd/m 2 ) at low voltages (<10 V). , Also, device engineering has been proposed to improve overall performances, including for example enhancement of the outcoupling efficiency, dual gate architectures for a more balanced hole and electron charge transport, and nonplanar source and drain electrodes to improve charge injection. , …”
Section: Introductionmentioning
confidence: 99%